2005
DOI: 10.1007/s11336-003-1078-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Modeling of response speed and accuracy with mixed and conditional regression

Abstract: time limit tests, conditional accuracy function, speed-accuracy tradeoff, conditional logistic regression, Cox regression, mixed regression, multilevel analysis, latent trait, mental rotation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 31 publications
0
59
0
1
Order By: Relevance
“…A commonly suggested transform for RT data is the logarithmic transform (Keppel & Wickens, 2004;Van Breukelen, 2005), which will reshape the distribution of RT data so that its heavy right tail is removed and it becomes more akin to a normal distribution. A mixed model analysis of log-transformed RTs resulted in the same significance levels as in model 1 but improved the distribution of residuals (Fig.…”
Section: Regression Diagnostics and Transformsmentioning
confidence: 99%
“…A commonly suggested transform for RT data is the logarithmic transform (Keppel & Wickens, 2004;Van Breukelen, 2005), which will reshape the distribution of RT data so that its heavy right tail is removed and it becomes more akin to a normal distribution. A mixed model analysis of log-transformed RTs resulted in the same significance levels as in model 1 but improved the distribution of residuals (Fig.…”
Section: Regression Diagnostics and Transformsmentioning
confidence: 99%
“…In experimental research, this is obtained as a proportion-correct conditioning on observed response time for each time-limit condition. For both SATF and CAF, a certain person ability and item difficulty are assumed to be given (i.e., these parameters are kept constant; Roskam, 1997;van Breukelen, 2005). Experimental research typically computes group means to investigate SATF and CAF.…”
Section: Speed-accuracy and Speed-ability Trade-offmentioning
confidence: 99%
“…The SATF is supposed to increase monotonically; whereas, for the CAF other forms may also be observed depending on the difference between mean correct response time and mean incorrect response time (Heitz, 2014;Luce, 1986). For instance, an erroneous process associated with both a long response time and an incorrect response would produce a decreasing CAF (van Breukelen, 2005).…”
Section: Speed-accuracy and Speed-ability Trade-offmentioning
confidence: 99%
See 2 more Smart Citations